Andrew Wyeth and the Wyeth Tradition, or “the Anxiety of Influence” - Helena Lamouliatte (Angles)
This article aims at assessing the true impact of the Wyeth tradition on the art of the American painter, Andrew Wyeth. Indeed, from an early age, the art prodigy was tutored by his father, the famous illustrator and painter N. C. Wyeth. Parallels were also drawn later between the younger figurative painter and his father’s teacher, the renowned illustrator Howard Pyle. However, we contend that the fabrication of this dynasty of American realists has done more harm than good to the critical reception of Andrew Wyeth’s art. Since the mid-1960s, Wyeth’s images have been vilified by most critics and art historians who focus on their supposedly illustrative and theatrical tricks. Nevertheless, some of them hint at a dark and less congruent dimension in Wyeth’s art, while being unable to pinpoint it precisely. By examining more closely Wyeth’s compositional strategy and pictorial technique in the light of his predecessors, this paper suggests that the artist has created a very personal and original synthesis of European and American influences, with a deep Gothic undercurrent. Wyeth’s problematic relationship with his father has also generated a range of obsessive visual tropes betraying his struggle, as a man and as an artist, with what Harold Bloom called “the anxiety of influence”. Lastly, a thorough analysis of some of his occasional self-portraits will attempt to shed light on Wyeth’s complex and morbid depiction of the figure of the artist as a troubled soul.